Foolish hearts - Williams, Synithia (Williams, Synithia. Jackson Falls., 2021)
When she inherits a fortune and multi-million dollar business from her paternal grandmother, Ashiya Walters uses this opportunity to start over and convince her first love, Russell Gilchrist, to give her another chance.